Pelayanan Pendidikan Di Rumah Berbasis Ramah Anak Di Era Pandemi Covid-19 Koping Strategi Dan Konsep Diri Orang Tua Siswa - Suhardin Suhardin (Al-Ulum: Jurnal Pendidikan Islam, 2021)
The Covid-19 pandemic has been widely researched in terms of its impact on social, cultural and political life, some have also examined the implementation of Distance Learning. This study describes the service of students' parents towards the implementation of child-friendly in the home based learning and relation to coping strategies and self-concept. Conducted in Jakarta by taking eighty sampling obtained by simple random sampling, using correlational quantitative methods, processing statistical data with person product moment, resulting in findings that there is a significant relationship between coping strategies and self concept with service parents of students towards the implementation of child-friendly home-based learning. Thus, to improve the quality of services and the continuity of the learning program at home, it is necessary to develop coping strategies and self-concept of the parents of students, as part of the policy for Distance Learning program intervention.Keyword: Educational Service in the home, Child-Frendly base, Covid-19 pandemic, Strategy coping, The Self-concept.